2006
DOI: 10.2174/157016106778521634
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and Vascular Smooth Muscle

Abstract: Leptin has received extensive attention as an endogenously produced satiety factor. Although once considered to be solely derived from adipose tissue, it is now apparent that leptin can be produced by various tissues including those comprising the cardiovascular system such as blood vessels and cardiomyocytes. Moreover, leptin receptors (OBR) have been identified in cardiovascular tissues. The increased cardiovascular risk associated with obesity is well known and many of the effects of leptin appear to be com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 109 publications
0
4
0
Order By: Relevance
“…It is secreted by adipocytes and binds to the hypothalamic leptin receptor (Ob-R) to enhance metabolism and reduce appetite [ 4 ], thereby increasing energy expenditure and decreasing energy intake. It is a product of the ob gene [ 5 ] and is associated with obesity, since a higher adipose tissue mass results in elevated leptin levels [ 6 ].…”
Section: Leptinmentioning
confidence: 99%
See 1 more Smart Citation
“…It is secreted by adipocytes and binds to the hypothalamic leptin receptor (Ob-R) to enhance metabolism and reduce appetite [ 4 ], thereby increasing energy expenditure and decreasing energy intake. It is a product of the ob gene [ 5 ] and is associated with obesity, since a higher adipose tissue mass results in elevated leptin levels [ 6 ].…”
Section: Leptinmentioning
confidence: 99%
“…Several studies have shown that the functional leptin receptor is also found in a variety of organs such as the heart, liver, kidneys, and pancreas [ 9 13 ]. It is located on cardiomyocytes [ 14 ], vascular smooth muscle cells [ 5 ], endothelial cells [ 15 ], myometrium [ 16 ], and cerebral and coronary vessels [ 17 , 18 ]. Therefore, this hormone has a wide range of pleiotropic effects, affecting the cardiovascular, nervous, immune, and reproductive systems [ 19 21 ].…”
Section: Leptinmentioning
confidence: 99%
“…Leptin is a 16 kDa protein that is the product of the ob gene (Zeidan and Karmazyn, 2006 ) and found in excessive levels in obesity (Sinha et al, 1996 ). It reduces appetite and increases energy expenditure, but also found to exert pleiotropic effects on several physiological systems, such as the nervous, immune, reproductive, and cardiovascular systems (Zeidan et al, 2006 ; Karmazyn et al, 2008 ; Fernández-Riejos et al, 2010 ; Zuure et al, 2013 ; Procaccini et al, 2014 ; reviewed by Ghantous et al, 2015a ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to adipocytes, leptin is produced by other kinds of cells including cardiomyocytes and VSMCs ( Zeidan et al, 2005 ; Matsui et al, 2007 ). Different studies have shown that the functional leptin receptor, leptin receptor b (OBRb), is found in a variety of cells such as VSMCs ( Zeidan et al, 2005 ; Zeidan and Karmazyn, 2006 ), cardiomyocytes ( Rajapurohitam et al, 2003 ), myometrial cells ( Markowska et al, 2005 ), endothelial cells ( Mutze et al, 2006 ), and T-lymphocytic cells ( Martin-Romero et al, 2000 ; Lord et al, 2002 ). Therefore, this hormone has a wide range of pleiotropic effects and affects the cardiovascular, nervous, reproductive, and immune systems ( Lord et al, 1998 ; Margetic et al, 2002 ; Rahmouni and Haynes, 2004 ).…”
Section: Introductionmentioning
confidence: 99%